2017
DOI: 10.4236/ojrm.2017.62002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Responding Knee Pain with Osteoarthritis, Meniscus and Ligament Tears Treated with Ultrasound Guided Autologous, Micro-Fragmented and Minimally Manipulated Adipose Tissue

Abstract: Background: Chronic knee pain from advanced osteoarthritis is often associated with tears in the fibro-cartilaginous meniscus and cruciate ligaments. The result is substantial pain and impairments and loss of daily function, thus limiting activity and quality of life. These often include pain, loss of range of 116 motion, inability to elevate the leg, pain increased with activity and gradual worsening over time. This represents a challenging clinical picture for which few non-surgical options are available. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…As a group, the study sample showed clinically meaningful improvement in pain, function, and QOL measures despite having previously failed other treatments for their knee pain. These results were similar to two published case reports where individuals with history of knee pain following meniscus tear in the setting of degenerative osteoarthritis were treated with ultrasound-guided intra-meniscal MFAT injections [ 12 , 35 ]. All subjects avoided the need for APM for their knee pain during the study period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a group, the study sample showed clinically meaningful improvement in pain, function, and QOL measures despite having previously failed other treatments for their knee pain. These results were similar to two published case reports where individuals with history of knee pain following meniscus tear in the setting of degenerative osteoarthritis were treated with ultrasound-guided intra-meniscal MFAT injections [ 12 , 35 ]. All subjects avoided the need for APM for their knee pain during the study period.…”
Section: Discussionsupporting
confidence: 90%
“…This may be compared with the cross-over rates from conservative management to APM in the Katz study as high as 21–30% at six to 14 months in various randomized controlled trials [ 36 ]. Furthermore, no participants reported serious adverse events after the procedure, which is consistent with other studies evaluating the effects of intra-articular MFAT [ 12 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Processed MFAT has been used as regenerative treatment for the management of musculoskeletal conditions such as knee osteoarthritis , shoulder pain secondary to osteoarthritis and rotator cuff tear , and osteochondral defects of the talus . In addition, case reports have reported improvement in pain and function scores after intra‐articular injection of MFAT in the setting of knee osteoarthritis and meniscal tear . Furthermore, a case report has been presented on this use of this device in the successful treatment of a degenerative meniscal tear in a triathlete .…”
Section: Addressing the Treatment Gap—orthobiologicsmentioning
confidence: 99%
“…When compared to enzymatically derived MSCs, mechanically derived MSCs have superior differentiation potential with larger secretome content and more diverse exosome content without disruption of vascular stroma [66,67]. This method is purely mechanical with no chemical additives used; thus, showing promising results that power the method of nonenzymatic harvesting of stem cells derived adipose tissue [19,[68][69][70][71][72].…”
Section: Issn: 2334-2846mentioning
confidence: 99%